Short-wavelength asymptotics of time correlation functions - Ignatyuk, V.V. (Condensed Matter Physics, 2001)
Short–wavelength asymptotics of time correlation functions (TCF) of simple
classical fluids is considered in the framework of short time expansion.
The explicit expressions for zeroth time moments up to the 8-th order of
cumulant are presented in the framework of additive approach. It is shown
that unlike the dynamic structure factor which is found to have Gaussian
form in short-wavelength limit, nongaussian corrections are present in TCF
“density–energy” and “energy–energy”. The comparison with generalized
collective modes approach as well as data for quantum liquids is discussed. Короткочасова асимптотика часових кореляційних функцій (ЧКФ)
простих рідин розглядається в рамках методу розкладу за малими
часами. Вирази для нульових часових моментів з точністю до 8-го
кумулянта представлені в наближенні адитивного підходу. Показано, що на відміну від динамічного структурного фактора, який має
гаусову форму в короткохвильовій границі, в ЧКФ “густина–енергія”
та “енергія–енергія” наявні негаусові поправки. Результати порівнюються з концепцією узагальнених колективних мод та даними для
квантових рідин.